2021
DOI: 10.3389/fendo.2021.613248
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Targeted Therapy in Adrenocortical Cancer

Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy with a poor prognosis. The current treatment standards include complete surgical resection for localized resectable disease and systemic therapy with mitotane alone or in combination with etoposide, doxorubicin, and cisplatin in patients with advanced ACC. However, the efficacy of systemic therapy in ACC is very limited, with high rates of toxicities. The understanding of altered molecular pathways is critically important to identify effective treatment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…with immunotherapy), have been evaluated for ACC. 49 , 78 82 Targets and pathways still open for clinical exploration include the Wnt/beta-catenin signaling pathways; SF-1, as commonly over regulated transcription factor; ACAT1, an enzyme involved in the cholesterol metabolism and initially investigated for cardiovascular disease but displaying significant adrenal toxicities; the estrogen pathway, as well as FGR inhibitors. 67 , 77 Some experts have suggested that in view of the low efficacy of EDP-M, upfront targeted therapy should be discussed if a new drug or target is available, followed by EDP-M in the case of progression only.…”
Section: Systemic Treatment – Are We Making Progress?mentioning
confidence: 99%
“…with immunotherapy), have been evaluated for ACC. 49 , 78 82 Targets and pathways still open for clinical exploration include the Wnt/beta-catenin signaling pathways; SF-1, as commonly over regulated transcription factor; ACAT1, an enzyme involved in the cholesterol metabolism and initially investigated for cardiovascular disease but displaying significant adrenal toxicities; the estrogen pathway, as well as FGR inhibitors. 67 , 77 Some experts have suggested that in view of the low efficacy of EDP-M, upfront targeted therapy should be discussed if a new drug or target is available, followed by EDP-M in the case of progression only.…”
Section: Systemic Treatment – Are We Making Progress?mentioning
confidence: 99%
“…Due to a slower onset of action, it should be used in combination with other drugs, like metyrapone, to control significant cortisol overproduction 6. Serum levels of mitotane must be monitored and target levels are 14–20 µg/mL 1 4. Mitotane is a lipophilic molecule with a long half-life and high doses of mitotane might lead to significant adverse reactions: nausea, vomiting, diarrhoea, adrenal insufficiency, increase of hepatic enzymes, hypercholesterolemia and hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, ACC is mostly sporadic, although, it can be diagnosed in the context of hereditary syndromes, such as Li-Fraumeni syndrome, Lynch syndrome, familial adenomatous polyposis and multiple endocrine neoplasia type 1 1. The prognosis of patients with ACC is generally poor, partly due to the advanced stage at diagnosis, with a median overall survival about 4 years 3 4. Most common sites of metastasis are lymph nodes, lungs, liver and bone 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies performed whole-exome sequencing (WES) on 45 and 91 ACC samples [ 5 , 6 ]. The authors report a mean somatic mutation rate of 0.6 and 0.9 mutations per megabase.…”
Section: Introductionmentioning
confidence: 99%